B agree
A,c, d don’t make sense
Answer:
A)16
Step-by-step explanation:
Given
f(x)=5x^2+9x-2
Remainder theorem states that when f(x) is divided by x-a then the remainder can be calculated by calculating f(a).
Now Using the remainder theorem to divide 5x^2+9x-2 by x+3 to find the remainder:
f(x)=5x^2+9x-2
f(-3) = 5(-3)^2 +9(-3) -2
=5(9) - 27 -2
= 45-29
= 16 !
Step-by-step explanation:
2x2 + 10 - 3x - 3 + 3
Solving like terms
2x2 - 3x + 10
Option B is the correct answer
Answer:D. The sign of each y- coordinate change.
Step-by-step explanation: because everything on the X axis stayed the same but on the Y axis it decreased